The Influence of Organizational Culture and Compensation on Employee Job Satisfaction at PT. Swabina Gatra Outsourcing Division - Friska Diva Lisandi; Heru Baskoro (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study aims to analyze the impact of organizational culture and compensation on job satisfaction of outsourcing employees. Data were collected through a survey of 98 employees. From this population, the sample taken for this study was 79 employees according to the Slovin Formula Calculation. The sampling technique used is the sampling technique with the Slovin Formula, namely n = N / (1 + Ne ^ 2) the result of the calculation of population members. Organizational Culture (X1) has a positive and significant effect on Job Satisfaction (Y). This proves that efforts to build and maintain a strong, supportive, and aligned organizational culture with employee values are important factors that can directly increase job satisfaction at PT. Swabina Gatra. Compensation (X2) has a positive and significant effect on Job Satisfaction (Y). These findings confirm that employee perceptions of the fairness and appropriateness of the compensation system, including salary, benefits, and especially expected incentives, are crucial drivers of job satisfaction. This confirms that the synergistic combination of a positive work environment and a fair reward system is a dominant factor in creating job satisfaction in the PT. Swabina Gatra environment.